SWI3 subunits of SWI/SNF complexes in Sweet Orange (Citrus sinensis): genome-wide identification and expression analysis of CsSWI3 family genes - Yinchun Li; Mengjie Xu; Dingwang Lu; Dengliang Wang; Shengchao Liu; Shaojia Li (Fruit Research, 2024)
SWI3 proteins as the core accessory subunits of SWI/SNF chromatin remodeling complexes (CRCs) could jointly take part in the genome epigenetic regulation upon disrupting the interaction between DNA and histones, ulteriorly regulating the accessibility of DNA-binding proteins or TFs to DNA. Research on chromatin remodeling complexes in plants lags behind yeast and animals, however, the last decade has witnessed an intensive effort to enhance our understanding of identification, characterization and molecular mechanisms of CRCs in Arabidopsis which provided the information for further studies in other plant species. So far, genome-wide identification of SWI3 family in citrus has not been reported. Here, four CsSWI3 genes based on Citrus sinensis genome were identified and clustered into four subfamilies. According to conserved domains and motifs analysis, we found that each CsSWI3 protein contained three conserved domains and the members in the same subfamily showed strong similarity with those in Arabidopsis. All of the CsSWI3 members were localized in the cell nucleus, which was consistent with the role as the subunit of CRCs. Analysis of promoter cis-regulatory elements indicated that CsSWI3 genes may be involved in stress response, phytohormone response and growth and development of citrus. Meanwhile, they were expressed extensively in citrus tissues and disparate development stages in fruit. We found that the expression level of CsSWI3A, CsSWI3B and CsSWI3C are positively correlated with sugar content during fruit development, especially for CsSWI3B. This study provides comprehensive information for the CsSWI3 gene family and sets a basis for its function identification in citrus.